2019
DOI: 10.1002/cb.1772
|View full text |Cite
|
Sign up to set email alerts
|

Human crowding and store messiness: Drivers of retail shopper confusion and behavioral intentions

Abstract: With today's cut‐throat competition, brick and mortar retailers are engaging in various in‐store elements like ambience, visual design, and social factors to entice consumers. However, these environmental stimuli if not used properly can lead to retail shopper confusion that can negatively influence shopper behavioral intentions. Drawing on the theoretical argument that information overload facilitates retail shopper confusion, two experimental studies are conducted. The findings of both studies suggest a main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 75 publications
3
21
0
1
Order By: Relevance
“…A pre-test was conducted to examine the manipulation of the social crowding in study 4 increased feelings of crowding. The manipulation was adapted from the study of Coskun et al (2019) . 85 participants were recruited online ( M age = 24.53, SD = 4.49, age range 18–35, female 50.59%).…”
Section: Methodsmentioning
confidence: 99%
“…A pre-test was conducted to examine the manipulation of the social crowding in study 4 increased feelings of crowding. The manipulation was adapted from the study of Coskun et al (2019) . 85 participants were recruited online ( M age = 24.53, SD = 4.49, age range 18–35, female 50.59%).…”
Section: Methodsmentioning
confidence: 99%
“…To measure in-store hiding behaviour, a three-item scale developed by Gupta and Gentry (2016b) was adopted. To check the manipulation of human crowding and store messiness, items were adopted from the study done by Coskun et al (2019). Also, perceived realism of the scenario and adaptation of the shopper to the scenario were measured to understand the believability of the study.…”
Section: Methodsmentioning
confidence: 99%
“…High influx of consumers can lead to disorganized shelves, unsorted merchandise and messy racks within the store, while they try to find some products of interest. Further, recent study done by Coskun et al (2019) suggested that both human crowding and store messiness lead to retail shopper confusion that affects consumers' behavioural intentions such as spending time in the store, store patronage and revisit intentions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of the application of consumer confusion in different contexts, scholars have worked across a diverse range of products and services. Confusion has been explored in physical retailing (Coskun et al, 2019;Shiu and Tzeng, 2018;Shiu, 2017;Garaus and Wagner, 2016;Garaus et al, 2015;Wobker et al, 2015), internet retailing (Garaus, 2018), mobile phones and electronic products (Turnbull et al, 2000;Ghosh and Rao, 2014;Leek and Kun, 2006), organic and nutritional food products (Chryssochoidis, 2000;Spiteri Cornish and Moraes, 2015;Leek et al, 2015), prescription drugs (Amoozegar et al, 2017), green products and eco-labels (Moon et al, 2017;Chen and Chang, 2013), watches (Mitchell and Papavassiliou, 1997), apparels (Stanton and Paolo, 2012) and the wine industry (Drummond and Rule, 2005). In the services area, the importance of confusion has been highlighted in the health-care sector (Chauhan and Sagar, 2020;Gebele et al, 2014), financial services (Shukla et al, 2010), higher education sector (Drummond, 2004) and online tourism services (Lu et al, 2016;Lu and Gursoy, 2015).…”
Section: Application In Different Contextsmentioning
confidence: 99%